White protectionism in America - Smith, RM; King, D (Cambridge University Press, 2020)
Critics charge President Donald Trump with racism, but he insists he opposes bigotry and is an American nationalist, not a white nationalist. This paper uses analysis of Trump’s campaign rhetoric, his administration’s policies, and their reception to assess these rival claims. In his campaign, Trump narrated American identity as a tale of lost greatness in which a once-unblemished America gave way to globalist elites who have victimized many Americans, particularly traditionalist, predominantly white Christian Americans. His policies have systematically expanded protections for such Americans and sought to increase their share of the American electorate and citizenry, while reducing or eliminating initiatives designed to assist and increase the numbers of non-white, non-Christian American voters and citizens. The evidence thus shows that although Trump does not explicitly endorse white nationalism, his rhetoric and policies articulate not a consistent race-blind nationalism, but a vision of white protectionism.